BONINITES FROM THE KOPAONIK AREA (SOUTHERN SERBIA): NEW EVIDENCES FOR SUPRASUBDUCTION OPHIOLITES IN THE VARDAR ZONE - Marroni, Michele; Pandolfi, Luca; Saccani, Emilio; Zelic, Mario (Ofioliti, 2004)
Fragments of Jurassic oceanic basins are preserved along two main alignments in the Dinaric-Hellenic belt. The western alignment, extending from western Greece to Croatia, is relatively well known, whereas the eastern, represented by the ophiolites of the Vardar zone, running from eastern Greece to Serbia, has been poorly investigated. In this paper, we provide new evidences for the occurrence of boninitic lavas in the Kopaonik area belonging to the Vardar zone. These rocks have been found in a sheeted dyke complex closely associated to harzburgitic mantle tectonites. This finding implies that, in contrast with previous interpretations, the Vardar zone is characterized by ophiolites originating in a suprasubduction zone setting. The occurrence of boninitic rocks gives important constraints for the geodynamic recostruction of the Dinaric-Hellenic belt.